Mass appraisal methods: an international perspective for property valuers - Taltavull, Paloma (International Journal of Strategic Property Management, 2009)
Mass appraisal methods: an international perspective for property valuers, Tom Kauko and Maurizio d’Amato (Eds.), Hardcover, Wiley‐Blackwell, August 2008, 360 pages. ISBN: 978–1–4051–8097–9 First Publish Online: 18 Oct 2010